Diastereo- and Enantioselective Hydrogenative Aldol Coupling of Vinyl Ketones: Design of an Effective Monodentate TADDOL-Based Phosphonite Ligand - Bee, Cisco (2008)
[Image: see text] We report the first enantioselective reductive aldol couplings of vinyl ketones, which required the design of a novel monodentate TADDOL-based phosphonite ligand. Specifically, hydrogenation of commercially available methyl vinyl ketone (MVK) or ethyl vinyl ketone (EVK) in the presence of aldehydes using chirally modified cationic rhodium catalysts produces aldol adducts 1b-7b and 1c-7c with excellent levels of diastereo- and enantiocontrol. Through the use of (R,R)-ligand or (S,S)-ligand good levels of catalyst-directed diastereofacial selectivity are achieved in hydrogenative aldol couplings of MVK and EVK to glyceraldehyde acetonide, as demonstrated by the formation of aldol adducts 6b, 6c, 7b, and 7c. The absolute stereochemical assignment of adducts 1b-5b and 1c-5c was made in analogy to that determined for the 5-bromophthalimido derivative of aldol adduct 2b, which was established by single crystal x-ray diffraction analysis using the anomalous dispersion method. A structure of the catalyst ligand complex [Rh(COD)(Ligand-Q)(2)]OTf has been established by single crystal x-ray crystal, as reported in the supporting information.